Diversity of species and geographic distribution of tick-borne viruses in China - Wu, Yi; Zhou, Qian; Mao, Meihan; Chen, Huangliang; Qi, Rui (Frontiers in Microbiology, 2024)
Tick-borne pathogens especially viruses are continuously appearing worldwide, which have caused severe public health threats. Understanding the species, distribution and epidemiological trends of tick-borne viruses (TBVs) is essential for disease surveillance and control. This study aimed to collect data from publicly available databases and published literature for summary and analysis of epidemiologic features of TBVs in China. Eighteen TBVs from eight genera of five families were prevalent in China. They were widely distributed but the specific ranges of viruses from different families still varied. Seven TBVs belonging to the genus Orthonairovirus of the family Nairoviridae such as Nairobi sheep disease virus (NSDV) clustered in the Xinjiang Uygur Autonomous Region (XUAR) and northeastern areas of China. All viruses of the family Phenuiviridae except Severe fever with thrombocytopenia syndrome virus (SFTSV) were novel viruses that appeared in the last few years, such as Guertu virus (GTV) and Tacheng tick virus 2 (TcTV-2). They were mainly distributed in the central plains of China. Jingmen tick virus (JMTV) was distributed in at least fourteen provinces and had been detected in more than ten species of tick such as Rhipicephalus microplus and Haemaphysalis longicornis, which had the widest distribution and the largest number of vector ticks among all TBVs. Parainfluenza virus 5 (PIV5) and Lymphatic choriomeningitis virus (LCMV) were two potential TBVs in Northeast China that could cause serious diseases in humans or animals. Five genera of ticks played an important role in the